Evidence-Based Practice in Higher Education: Teacher Educators' Attitudes, Challenges, and Uses - Diery, Annika; Vogel, Freydis; Knogler, Maximilian; Seidel, Tina (Frontiers in Education, 2020)
Teacher educators are encouraged to promote evidence-based practice in teaching and to use evidence for their own teaching. In the present study, teacher educators' attitudes, perceived challenges, and uses regarding evidence-based practice are described. Moreover, the extent to which personal factors are related to the use of evidence is investigated. In an exploratory study, 58 teacher educators from higher education participated in an online survey. The results reveal that teacher educators generally have a positive attitude toward evidence-based practice. They use evidence regularly, both for individual learning and for teaching purposes. Furthermore, the study reveals that teacher educators with more experience in research and teaching have a more positive attitude toward evidence-based practice and higher uses of evidence. In comparison, less experienced teacher educators perceived more challenges. It is discussed, how teacher educators can be supported in their professional learning, particularly in light of the increasing scientific knowledge base in education.